Edukasi Pencegahan Stunting di 1000 Hari Pertama Kehidupan di Desa Tolisu dan Desa Rusa Kencana Kabupaten Banggai - Dewi T. Lamato; Zamli Zamli (Jurnal Pengabdian Masyarakat JUPEMANDO, 2025)
Stunting remains a major public health problem in Indonesia, with lasting effects on children’s growth and development. The first 1,000 days of life, from pregnancy to the age of two, is a critical period to prevent stunting. Limited knowledge of nutrition, parenting, and healthy behaviors among pregnant women and families contributes to its high prevalence. This community service aimed to improve pregnant women’s knowledge about stunting prevention through participatory education. The activity was conducted in Tolisu and Rusa Kencana Villages, Toili II Health Center, Banggai, in July 2025 with 30 pregnant women. Counseling sessions used the Maternal and Child Health handbook and interactive discussions, with knowledge assessed using pre-test and post-test. Results showed a 42% increase in average scores (from 8.9 to 9.5). The program improved awareness of balanced nutrition, exclusive breastfeeding, and healthy practices. This educational intervention proved effective and can be sustained in rural communities.